1999
DOI: 10.1039/a902766a
|View full text |Cite
|
Sign up to set email alerts
|

Determination of carbonyls using liquid chromatography-mass spectrometry with atmospheric pressure chemical ionization

Abstract: A liquid chromatographic method for the determination of aldehydes and ketones based on mass spectrometric detection is described. Recently developed modular derivatizing agents are employed for analysis. These hydrazine reagents, e.g. 4-dimethylamino-6-(4-methoxy-1-naphthyl)-1,3,5-triazine-2-hydrazine (DMNTH), react with the carbonyl compounds with the formation of the respective hydrazones, which are separated by HPLC-MS with atmospheric pressure chemical ionization in the positive mode. Electrospray ionizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Their structures are depicted in Scheme 1. These reagents not only fluoresce strongly, they can also be used in conjunction with massspectrometric detection, because they are readily ionized by electrospray ionization (ESI) or atmospheric-pressure chemical ionization (APCI) in the positive-ion mode [15]. Because of its rapid reaction with aldehydes and ketones, DMNTH has been successfully used for the determination of carbonyl compounds in water [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their structures are depicted in Scheme 1. These reagents not only fluoresce strongly, they can also be used in conjunction with massspectrometric detection, because they are readily ionized by electrospray ionization (ESI) or atmospheric-pressure chemical ionization (APCI) in the positive-ion mode [15]. Because of its rapid reaction with aldehydes and ketones, DMNTH has been successfully used for the determination of carbonyl compounds in water [16].…”
Section: Introductionmentioning
confidence: 99%
“…A chromophoric or fluorophoric group, a reactive moiety, and a third functionality, e.g. to modify the polarity of the complete reagent in the desired way, are coupled to cyanuric chloride by means of nucleophilic substitutions or Friedel-Crafts alkylations [14,15,16]. 4-N,N-Dimethylamino-6-(4′-methoxy-1′-naphthyl)-1,3,5-triazine-2-hydrazine (DMNTH), and Nmethyl-4-N′,N′-dimethylamino-6-(4′-methoxy-1′-naphthyl)-1,3,5-triazine-2-hydrazine (MDMNTH) have been identified as being particularly favourable.…”
Section: Introductionmentioning
confidence: 99%
“…17 As is now common in recent analytical developments, GC is frequently substituted by HPLC analysis. [9][10][11]15,16,24 In these studies, DNPH derivatives were found most useful. Single-stage mass spectrometry is more specific than UV, and detection limits may reach the lowpicogram range.…”
mentioning
confidence: 98%
“…The most common method is derivatization with 2,4-dinitrophenylhydrazine (DNPH) reagent. 15 Alternatives include derivatization with 4-dimethylamino-6-(4-methoxy-1-naphthyl)-1,3,5-triazine-2-hydrazine, 16 and the use of pentafluorophenyl-, 2-chloro-and 2,4-dichlorophenylhydrazine derivatives. 17,18 Analysis is often performed using gas chromatography (GC), [18][19][20] with flame ionization (FID), 19 occasionally with mass spectrometric 2,21 or ECD 17,18 detection.…”
mentioning
confidence: 99%
“…There are several reports on the use of DMNTH as a derivatization reagent. Examples are the derivatization of carbonyl containing compounds followed by chromatographic separation and detection by atmospheric pressure chemical ionisation (APCI) mass spectrometry and in water samples [10,11]. The optimised parameters necessary for the separation of DMNTH derivatized carbonyl compounds by reversed phase capillary electrochromatography (CEC) have been described [12].…”
Section: Introductionmentioning
confidence: 99%